Achieving sustainable and climate‐resilient fisheries requires marine ecosystem forecasts to include fish condition. Issue 5 (18th May 2021) - Bolin, Jessica A.; Schoeman, David S.; Evans, Karen J.; Cummins, Scott F.; Scales, Kylie L.
Abstract: Marine ecosystem forecasting is an important innovation in fisheries science with considerable value for industry and management, providing new data‐driven means of predicting the distribution and availability of commercially exploited fish stocks over a range of timescales, including near‐real‐time and seasonal. Marine ecosystem forecasting is rapidly advancing as a field, yet tools produced for fisheries to date focus primarily on predicting species distributions. The next generation of marine ecosystem forecasting products could be enhanced by also incorporating predictions of biological characteristics of fish caught, such as body condition and epidemiological status, thereby expanding the utility of these methods beyond predicting distribution alone. Improving the biological dimensions of marine ecosystem forecasting could allow for optimization of efficiencies in wild‐capture fisheries by minimizing discarding and waste and maximizing the value of landed fish. These advancements are of direct benefit to industry and management, address several of the United Nations Sustainable Development Goals pertaining to fisheries sustainability and have the potential to support the maintenance of global food and micronutrient security under rapidly changing environmental conditions. Here, we describe the current state of the art in marine ecosystem forecasting; review the physical‐biological linkages that underlie variability in the body condition of commercially valuable fish and shellfish with particular reference to marine climate change; and outline key considerations for the next generation of marine ecosystem forecasting tools for wild‐capture fisheries.